2016
DOI: 10.3906/sag-1411-169
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of hepatitis C virus genotypes among intravenous drug users in the Çukurova region of Turkey

Abstract: HCV genotypes seem to be different between the normal population and IVDUs according to studies worldwide. Among IVDUs, we detected a dominance of genotype 3 and genotype 2, which is apparently different from the normal population. The reason for this difference can be simply explained by infection through shared needles. However, there may still be a different immunological response in IVDUs, the investigation of which may lead to further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
(44 reference statements)
0
5
0
8
Order By: Relevance
“…This shift has been mainly attributed to IVDU becoming a significant mode of transmission (4,17). As in the rest of the world, previous studies have reported similar changes in HCV genotype distribution in Turkey, and it was also suggested that IVDU may be a factor in this shift (18,19).…”
Section: Discussionmentioning
confidence: 83%
“…This shift has been mainly attributed to IVDU becoming a significant mode of transmission (4,17). As in the rest of the world, previous studies have reported similar changes in HCV genotype distribution in Turkey, and it was also suggested that IVDU may be a factor in this shift (18,19).…”
Section: Discussionmentioning
confidence: 83%
“…Ayrıca HCV'ye karşı geliştirilen yeni nesil ilaçlar da hastalığın kesin tedavisin sağlayarak yayılımına engel olmaktadır (12) . Ülkemizde yapılan çalışmalarda, genotip 2'nin Akdeniz bölgesinde diğer bölgelere kıyasla daha fazla oranda gözlendiği bildirilmiştir (11,(19)(20)(21) . Akdeniz bölgesinde genotip 2 oranı Kandemir ve ark.…”
Section: Discussionunclassified
“…(21) tarafından yapılan çalışmada, %9.2 bulunurken, ülkemizde genotip 2'ye ait en yüksek oran Üçbilek ve ark. (11) tarafından %29.8 olarak belirtilmiştir. Üçbilek ve ark.…”
Section: Discussionunclassified
See 2 more Smart Citations